Studies on in vitro Antioxidant Activity of Marine Edible Seaweed From East Coastal Region, Peninsular Malaysia Using Different Extraction Methods - Tam, Siow Foon; Lian, Ai Ai; Kuppusamy, Palaniselvam; M. M., Yusoff; Natanamurugaraj, Govindan (Medwell Publishing, 2014)
In this present study the antioxidant activity of two edible seaweeds Eucheuma cottonii and Padina sp. were determined. The two extraction methods such as conventional and soxhlet were used to extract secondary metabolites by using methanol as a solvent medium. Total phenolic content of crude seaweed extracts were analysed by standard method. The different antioxidant assays 2,2-Diphenyl-1-Picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Power (FRAP) and β-carotene bleaching assays were studied. The DPPH and FRAP assays showed positive correlation with expressed higher total phenolic content of methanolic seaweed extracts. Also, β-carotene bleaching assay lower activity compare with BHT as reference control. IR spectra showed the phenolic related functional groups are present the seaweed extract. It mainly responsible for higher rate of antioxidant activity. The methanolic extracts of Padina sp. showed better radical scavenging and higher phenolic content than Eucheuma cottonii. Also, the soxhlet extraction showed higher yield and better radical scavenging activity compared to conventional method. Moreover, the studies confirmed both seaweeds are an effective candidate for the control the free radical scavenging activity.